Prevention of SARS-CoV-2 transmission during a large, live, indoor gathering (SPRING): a non-inferiority, randomised, controlled trial. Issue 3 (March 2022) - Delaugerre, Constance; Foissac, Frantz; Abdoul, Hendy; Masson, Guillaume; Choupeaux, Laure; Dufour, Eric; Gastli, Nabil; Delarue, Severine Mercier; Néré, Marie Laure; Minier, Marine; Gabassi, Audrey; Salmona, Maud; et al.
Summary: Background: Mass indoor gatherings were banned in early 2020 to prevent the spread of SARS-CoV-2. We aimed to assess, under controlled conditions, whether infection rates among attendees at a large, indoor gathering event would be similar to those in non-attendees, given implementation of a comprehensive prevention strategy including antigen-screening within 3 days, medical mask wearing, and optimised ventilation. Methods: The non-inferiority, prospective, open-label, randomised, controlled SPRING trial was done on attendees at a live indoor concert held in the Accor Arena on May 29, 2021 in Paris, France. Participants, aged 18–45 years, recruited via a dedicated website, had no comorbidities, COVID-19 symptoms, or recent case contact, and had had a negative rapid antigen diagnostic test within 3 days before the concert. Participants were randomly allocated in a 2:1 ratio to the experimental group (attendees) or to the control group (non-attendees). The allocation sequence was computer-generated by means of permuted blocks of sizes three, six, or nine, with no stratification. The primary outcome measure was the number of patients who were SARS-CoV-2-positive by RT-PCR test on self-collected saliva 7 days post-gathering in the per-protocol population (non-inferiority margin <0·35%). This trial is registered with ClinicalTrials.gov, NCT04872075 . Findings: Between May 11 and 25, 2021, 18 845 individuals registered on the dedicated website, and 10 953 were randomly selected for a pre-enrolment on-site visit. Among 6968 who kept the appointment and were screened, 6678 participants were randomly assigned (4451 were assigned to be attendees and 2227 to be non-attendees; median age 28 years; 59% women); 88% (3917) of attendees and 87% (1947) of non-attendees complied with follow-up requirements. The day 7 RT-PCR was positive for eight of the 3917 attendees (observed incidence, 0·20%; 95% CI 0·09–0·40) and three of the 1947 non-attendees (0·15%; 0·03–0·45; absolute difference, 95% CI −0·26% to 0·28%), findings that met the non-inferiority criterion for the primary endpoint. Interpretation: Participation in a large, indoor, live gathering without physical distancing was not associated with increased SARS-CoV-2–transmission risk, provided a comprehensive preventive intervention was implemented. Funding: French Ministry of Health. Translation: For the French translation of the abstract see Supplementary Materials section.